2008
DOI: 10.1111/j.1651-2227.2008.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression is associated with mother–infant interaction in preterm infants

Abstract: This study suggests that maternal depression may be a risk factor in the development of the mother-infant relationship between preterm infants and their mothers. Therefore, it would be important to identify signs of depression in mothers of preterm infants to offer early support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 27 publications
5
96
1
4
Order By: Relevance
“…Certain variables have been associated to alterations of the mother's mood, it has been suggested that high risk pregnancies, obstetric complications or prematureness all contribute to the development of depressive symptoms (Agoub, Moussaoui, and Battas, 2005;Davis, Edwards, Mohay, and Wollin, 2003;Korja et al, 2008;Piyasil and Pichaiyut, 2011;Verdoux, Sutter, Glatigny-Dallay, and Minisini, 2002;Verkerk, Pop, Van Son, and Van Heck, 2003;Vigod, Villegas, Dennis, and Ross, 2010). In births that produce neonatal complications (foetal suffering or hospitalization of the new-born) there is an increase of depressive symptoms (Blom et al, 2010).…”
Section: Socio-demographic and Clinical Variables And Postnatal Deprementioning
confidence: 99%
“…Certain variables have been associated to alterations of the mother's mood, it has been suggested that high risk pregnancies, obstetric complications or prematureness all contribute to the development of depressive symptoms (Agoub, Moussaoui, and Battas, 2005;Davis, Edwards, Mohay, and Wollin, 2003;Korja et al, 2008;Piyasil and Pichaiyut, 2011;Verdoux, Sutter, Glatigny-Dallay, and Minisini, 2002;Verkerk, Pop, Van Son, and Van Heck, 2003;Vigod, Villegas, Dennis, and Ross, 2010). In births that produce neonatal complications (foetal suffering or hospitalization of the new-born) there is an increase of depressive symptoms (Blom et al, 2010).…”
Section: Socio-demographic and Clinical Variables And Postnatal Deprementioning
confidence: 99%
“…They are: Global Rating Scales (GRS), 49 Barkin Index of Maternal Functioning (BIMF), 50 ParentChild Early Relational Assessment (PCERA), 51 Postpartum Maternal Attachment Scale (PMAS), 52 and Brown Scale of Interactions. 53 All demonstrated high internal consistency, except the GRS, whose study described no measure of reliability.…”
mentioning
confidence: 99%
“…Infants' gestational age, birth weight, length of hospitalization, and maternal stress did not correlate with maternal depressive symptoms (Korja et al, 2008;Mew et al, 2003).…”
Section: Relationships Between the Study Variablesmentioning
confidence: 98%
“…A number of investigators studied anxiety and depressive symptoms in parents of a term or preterm infants admitted in the NICU (Kong et al, 2013;Korja et al, 2008;Holditch-Davis et al, 2009;Padovani, Carvalho, Duarte, Martínez, & Linhares, 2009). …”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation